Emission scenario analysis for China under the global 1.5 °C target. Issue 5 (3rd September 2018) - Jiang, Kejun; He, Chenmin; Dai, Hancheng; Liu, Jia; Xu, Xiangyang
Abstract: In the Paris Agreement, there are targets set up for 2100 to be well below 2 °C. A more ambitious target of 1.5 °C also appears in the agreement. In order to address whether this target is achievable or not, studies about the 1.5 °C target's emission pathway are essential. Recently a few studies have presented modelling results of the global emission pathway for the 1.5 °C target. This paper presents an analysis for China under the global 1.5 °C pathway and budget, by looking at key options to go beyond the 2 °C target pathway. Similar to the global emission pathway, China's CO2 emissions have to be reduced quickly and reach zero emission between 2050 and 2060. China's energy system needs to make a rapid transition to much greater reduction in fossil fuel use from now on. End-use sectors need to increase electricity use significantly. Power generation will achieve negative emission before 2050. CCS will be widely used, and biomass energy with CCS (BECCS) must be adopted on a large scale by 2040. This is doable in China, but very near-term changes in policy are needed to make such a pathway happen.